Lower Kinetic Chain, Meet the Thinking Brain: A Scoping Review of Cognitive Function and Lower Extremity Injury Risk - Michaela A. Reyes; Mark O. Probasco; Trina N. Worby; Dylan E. Loertscher; Lyndsey K. Soderbeck; Wendy E. Huddleston (International Journal of Sports Physical Therapy)
The classic model of non-contact ACL injury includes environmental, anatomical, hormonal and biomechanical risk factors which directly impact either the amount of stress placed on the ligament or the relative capacity of ligament to withstand the forces placed on it. However, cognition also clearly plays a role in successful athletic performance, yet diminished cognitive function is rarely considered a risk factor for injury.